2022
DOI: 10.1038/s41598-021-04469-0
|View full text |Cite
|
Sign up to set email alerts
|

Functional cortical localization of tongue movements using corticokinematic coherence with a deep learning-assisted motion capture system

Abstract: Corticokinematic coherence (CKC) between magnetoencephalographic and movement signals using an accelerometer is useful for the functional localization of the primary sensorimotor cortex (SM1). However, it is difficult to determine the tongue CKC because an accelerometer yields excessive magnetic artifacts. Here, we introduce a novel approach for measuring the tongue CKC using a deep learning-assisted motion capture system with videography, and compare it with an accelerometer in a control task measuring finger… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…CKC seems to be a robust feature with potential for clinical rehabilitation; however, it was not used in this specific context [ 113 ]. The use of deep-learning-based motion capture to calculate CKC was successfully demonstrated by Maezawa et al [ 114 ] to map cortical areas involved in tongue movement. Another feature that can assist in evaluating somatosensory impairments based on the coherence between EEG and perturbed mechanical movement is position-cortical coherence (PCC).…”
Section: Discussionmentioning
confidence: 99%
“…CKC seems to be a robust feature with potential for clinical rehabilitation; however, it was not used in this specific context [ 113 ]. The use of deep-learning-based motion capture to calculate CKC was successfully demonstrated by Maezawa et al [ 114 ] to map cortical areas involved in tongue movement. Another feature that can assist in evaluating somatosensory impairments based on the coherence between EEG and perturbed mechanical movement is position-cortical coherence (PCC).…”
Section: Discussionmentioning
confidence: 99%
“…Since many decades it was known that the anterior region of the tongue has different receptive fields with a huge density of receptors. However, recent studies in humans showed perfectly how the touch on different regions elicit different muscle activity [9][10][11]. The sagittal part of the dorsal arch touches on the tongue lateral side and the anterior notch touches on the tongue tip, generating activation of styloglossus (as main muscle, considering that all tongue and related muscles will be also activated), having, as a result, tongue transversal size diminishing, dorsal elevation, and up-down movement of the tip [12][13][14].…”
Section: Mechanism Of Actionmentioning
confidence: 99%
“…In order to better analyze the motion state of dance performers, a method for analyzing human motion posture using the principle of feature plane similarity matching is proposed. Tis method simplifes the traditional calculation of Euclidean distance based on multiple identifcation points to the calculation of a feature plane feature vector and its included angle [22]. In this paper, the identifcation points of 21 key parts are simplifed into 7 feature planes to calculate the motion diference and correlation.…”
Section: Human Motion Pose Analysis Based On Feature Vectormentioning
confidence: 99%